Production of adsorbent charcoal from the Pequirind (Caryocar brasiliense) and application in wastewater treatment of textile industry through the adsorption - Lopes, Toni Jefferson; Patias, Samira Gabrielle Oliveira; Sávio, Juliana; Costelli, Murilo Cesar; Cancelier, Adriano; Silva, Adriano da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The pequi rind (Caryocar brasiliense) is a residue without technological application. Thus, the objective was to study the influence ofdifferent parameters in the process of obtaining carbon adsorbent without activation, of pequi rind, and its application in the removal of methylene blue dye. In the production of carbon adsorbent techniques of experimental design have been used to assess the influence of variables: initial mass of pequi rind and temperature and relative the yield carbon mass and mass concentration of dye on carbon. Thereafter, the carbon used in testing of kinetics adsorption and desorption of dye. The process afforded one region optimal for production of carbon that was 375 to 400°C and 66.15 to 75g, at a time of 20 minutes, and has been chosen the point of 400 °C and 66.15 g, having yield of 7% and the adsorption capacity of 68%. In tests of the kinetic equilibrium, time was 90 min for all tested concentrations of dye and assays desorption resulted in low percentages of removal of dye. It is concluded that pequi rind carbon is a adsorbent of low value, but without industrial applicability due low yield in mass and viability of recovery.